Advances in pharmacokinetic-pharmacodynamic modeling for anesthesia, 1987–2024: a review - Tulbah, Yara; Aljamaan, Ibrahim (Frontiers in Pharmacology, 2026)
In the field of individualized anesthesia, pharmacokinetic-pharmacodynamic (PKPD) models are crucial as they assist in determining the appropriate dosage for various patient groups. This research reviews the development of primary PKPD anesthetic models proposed in the literature from 1987 to 2024. The results from 33 studies are combined, offering a range of concepts from the earliest contributions, such as the “pharmacokinetic mass” concept of Shibutani et al. for fentanyl in obese patients, to the most recent developments in multi-input control strategies for managing anesthesia depth with propofol and remifentanil. Recent advancements are also discussed, including the propofol model proposed by Braathen et al. for severe obesity, which employs innovative scaling techniques to enhance dose accuracy. This study examines physiologically based modeling approaches, reviews traditional compartmental models, and highlights the use of nonlinear mixed-effects modeling. The review concludes by outlining future research aimed at creating more individualized, closed-loop anesthetic delivery systems, emphasizing significant developments in PKPD modeling and identifying limitations in the existing techniques.